Про підхід до проектування системи тестування знань з мови SQL - Широкопетлєва, Марія Сергіївна; Черепанова, Юлія Юріївна (НТУ "ХПІ", 2016)
Розглядаються питання проектування та розробки системи тестування знань з мови структурованих запитів до бази даних. Запропоновано критерії формування тестових наборів для тестування знань з мови структурованих запитів, наведена методика формування тестових завдань та оцінки проходження тестування. Визначено підходи до проектування програмної системи тестування знань з урахуванням можливості виконання запитів на модифікацію даних та зміну структури бази даних, з відкатом транзакції при помилці запиту редагування даних.

The problems of the design and development of knowledge testing system Structured Query Language was discussed in the article. Test systems are widely applied in the educational process. But evaluation of the level of knowledge of SQL has problems with their use. There are usage isolated transaction for CRUD operations and database recovering for database modification query (create, alter, drop). The method of test tasks formation was described. Also two criteria for the test tasks were proposed and formalized: criterion completeness and lack of intersection criterion. There are set in the test questions should cover all elements of the topic you being tested (criterion completeness). The lack of intersection criterion is checking to be only fragments of the tasks for which formulated questions. Difficulty levels for thematic units can be used for formation of the test results.
The approach to the design of system of testing knowledge of SQL
Keywords: автоматизована перевірка; мова структурованих запитів; СУБД; тестова база; automated testing; Structured Query Language; test task criteria